Geographic expansion, income diversification, and bank stability: Evidence from Vietnam - Tu D. Q. Le (Cogent Business & Management, 2021)
This study empirically examines the impact of geographic expansion and income diversification on bank stability in Vietnam between 2006 and 2015 using the system generalized method of moments (GMM). The findings show that in general geographic expansion can enhance bank stability while income diversification per se does not. The results also indicate that state-owned commercial banks could only benefit from geographic expansion rather than from income diversification. However, foreign ownership tends to promote bank stability when pursuing both strategies. Our research has implications for bank supervisors, policy-makers, and bank managers.
Keywords: G21; G28; G30; 650; Geographic diversification; income diversification; bank stability; Vietnam; GMM